2016
DOI: 10.1016/j.ijfatigue.2016.05.033
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heat treatment on very high cycle fatigue behavior in hot-rolled WE43 magnesium

Abstract: The role of crack initiation and short crack growth on fatigue life in the very high cycle fatigue regime (VHCF) is investigated for three heat treatments of the wrought magnesium alloy WE43. As-received (T5) WE43 with a relatively fine grain size was solution treated and aged to produce precipitation strengthened coarse-grained microstructures in the underaged and peak-aged (T6) conditions. Ultrasonic axial fatigue tests with a cyclic frequency of 20kHz were conducted using smooth specimens. Heat treatment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 68 publications
1
49
0
Order By: Relevance
“…Previous investigations on three cast magnesium alloys (AZ91, AM60, and AS21) by Papakyriacou et al delivered similar results of threshold stress intensity factors in ambient air, which were between 55% and 65% of the respective threshold value measured in vacuum. Adams et al investigated the propagation of short cracks in wrought WE43 alloy and found that growth rates in vacuum are nearly two orders of magnitude lower than in laboratory air. In vacuum, higher stress intensity factor amplitudes were necessary to further prolong cracks that had been previously initiated and propagated in ambient air.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations on three cast magnesium alloys (AZ91, AM60, and AS21) by Papakyriacou et al delivered similar results of threshold stress intensity factors in ambient air, which were between 55% and 65% of the respective threshold value measured in vacuum. Adams et al investigated the propagation of short cracks in wrought WE43 alloy and found that growth rates in vacuum are nearly two orders of magnitude lower than in laboratory air. In vacuum, higher stress intensity factor amplitudes were necessary to further prolong cracks that had been previously initiated and propagated in ambient air.…”
Section: Discussionmentioning
confidence: 99%
“…Threshold stress intensity factor amplitudes are in the range of 1.25 to 1.55 MPam 1/2 in ambient air but 2.1 to 2.7 MPam 1/2 in the inert environment . In differently heat‐treated wrought magnesium alloy WE43, fatigue crack growth of short cracks strongly decelerates or even stops, when the testing environment is changed from ambient air to vacuum …”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…73,132 The parameters of the cohesive law for crack propagation along various slip systems have been obtained using experimental (micro-beach marking) measurements of local crack growth rates within a grain. 127 This is coupled with Fig. 12.…”
Section: Fatigue Behavior Use Casementioning
confidence: 80%
“…A unique ultrasonic fatigue scanning electron microscope (UFSEM) was used to quantify the growth rates of cracks as they advance through grains and across grain boundaries. 127,128 Focused ion beam notches were placed in grain neighborhoods with specific characteristics (e.g., Schmid factors, misorientation). Detailed analysis of crack initiation lifetime, small crack propagation rates, crack interactions at grain boundaries and crack pathways in each grain were characterized, 129 an example of which is shown in Fig.…”
Section: Fatigue Behavior Use Casementioning
confidence: 99%